Knowledge, attitude, and practices towards lightning among vulnerable group: A case study on Agri farmers and fishermen - Md. Mostafizur Rahman; Ifta Alam Shobuj; Md. Mehedi Hasan Santo; Habib Mohammad Ali; Md. Tanvir Hossain; Edris Alam; Md. Kamrul Islam (Sustainable Environment)
Bangladeshi fishermen and Agri farmers are particularly at risk from lightning strikes. There is little evidence of this population’s response, especially in rural locations at risk of lightning strikes. This research aims to know how these vulnerable people in northeastern Bangladesh react to lightning. 582 Agri farmers and fishermen participated in our face-to-face Knowledge, Attitude, and Practice (KAP) survey. Multiple regression analyses and descriptive statistics have been performed. Even though lightning is frequent, none had ever participated in lightning training. About 81% did not hear anything about lightning in the news. However, almost 80% had lightning-related knowledge, and 90% had a positive attitude. Fewer than half of the people surveyed had taken any lightning practices. Knowledge is related to occupation, monthly income, location, attitude, and practices; (p <0.05). On the other hand, attitude was linked to factors including age, occupation, monthly income, geographic region, and knowledge. There was an association between practices with monthly income, location, and knowledge. Better lightning protection could be possible with more thorough lightning safety training. Relevant stakeholders such as government agencies, local authorities, and NGOs should take steps to change people’s responses to lightning. They can conduct massive lightning-related campaigns, implement improved safety procedures, and provide intensive training.